The relationship between parenting behavior and the personality of kindergarten children - Däschle, Johanna; Hofmann, Carmen; Wernicke, Jennifer; Ziegenhain, Ute; Montag, Christian; Kiefer, Markus (Frontiers in Psychology, 2023)
According to Cloninger’s biosocial model of personality touching upon temperament and character, personality development is a lifelong adaptive process that begins in early childhood. Similarly, theories of parenting behavior and attachment predict that associations between personality and parenting behavior should be found in young children. The present study therefore had the goal to investigate, whether associations between parenting behavior and personality in terms of Cloninger’s temperament and character dimensions previously found in adolescence and adults can already be observed in kindergarten children. This study therefore assessed personality in a sample of 324 kindergarten children (169 girls/155 boys) aged three to six years (Mage = 4.59, SD = 0.90). Parents rated their children’s temperament and character using the JTCI 3-6 R questionnaire, which has been specifically developed to measure personality dimensions in three to six-year-olds according to Cloninger’s model. Character traits (especially Self-Transcendence), which reach mature levels in adults, may not be reliably assessed in three-year-old children. Parenting behavior was documented using the DEAPQ-EL-GS self-report questionnaire measuring the parenting behavior dimensions Responsiveness and Demandingness. Correlation analyses revealed that responsive parenting behavior was positively related to the personality dimensions Reward Dependence, Self-Directedness, and Self-Transcendence. Demanding parenting behavior was positively related to the personality dimension Novelty Seeking, but negatively related to the personality dimensions Persistence, Self-Directedness and Cooperativeness. Although the cross-sectional design of our study prevents unequivocal conclusions about the causal direction of these associations, our results highlight possible differential consequences of responsive vs. demanding parenting behavior for personality development in children in line with theories of parenting behavior and attachment. Our results thus advance earlier work in adolescents and adults, by showing that parenting behavior influences the development of the child’s personality according to Cloninger’s biosocial model already in three to six-year-olds.